Studi Perbedaan Niat Beli Green Electricity Product Berdasarkan Gender - Tias Andarini Indarwati; Nindria Untarini (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2017)
Consumers adapt to this situation by considering environmental issue when shopping and  by their purchase behavior. The aims of this paper are examines of differences of environment awareness and purchase intentions between male and female of students of Surabaya State University. Secondly, examines also role linearly of environment awareness on purchase intentions. Examines role linearly of environment awareness on purchase intentions of green electricity product using simple linier regression analysis. The results indicate that there are no differences of environment awareness and purchase intentions at the students of Surabaya State University by gender. And finally, environmental awareness has also positive effect on purchase intentions. The results of this study have implications for marketers in identifying, designing, and managing marketing mix with consider discrepancy of purchase intentions in the green electricity product by gender.